Incidencia de la hiperlipidemias en adultos de 20 a 49 años a través del método fotocolorimetrico. Balzar de Vinces, cantón Vinces, provincia de Los Ríos, abril a octubre del 2014. - Díaz Piguave, Carlos Alberto (2014)
The hiperlipidemia is altered lipid levels in blood, either by TC increase, LDL-C and TG, or by a decrease in HDL-C. Due to its atherogenic action, this lipid disorder is considered one of the major risk factors for cardiovascular events. The aim of this study was to analyze the lipid profile in the community of Balzar Vinces, 2014. The sample consisted of 115 overweight patients, to whom Seles extracted a blood sample with a fast of 12-14 hours and were processed with photocolorimetric method. Descriptive statistics were applied, using the worksheet data analysis Distribution in adults 20-49 years of the average values ​​of the lipid profile were within normal ranges, presenting alterations from the 36 years. As for the index Catelli was found in low range in most patients in both genders, presenting atherogenic risk 22% of the population. The most frequent dislipidemia in Balzar Community Vinces was hiperlipidemia, increased LDL-C and decrease in HDL-C